Mainstreaming community-based forest management in West Sumatra: Social forestry arguments, support, and implementation - Asmin, Ferdinal; Darusman, Dudung; Ichwandi, Iin; Suharjito, Didik (Forestry Faculty, Universitas Hasanuddin, 2019)
Although social forestry in Indonesia is envisioned as a policy for recognizing local practices to forest management, research is still limited. This research describes conditions of social forestry policy in West Sumatra Province as a form of mainstreaming community-based forest management. This paper provides the context of social forestry arguments, its support, and subsequent implementation. The research approach is qualitative, using a case study method. Data collection was conducted through unstructured interviews, field observations, and document studies. The analysis used categorization and coding, historical analysis, document analysis, and descriptive policy analysis. The findings revealed that the arguments for social forestry schemes were based on the persistence of state forest conflicts, forest degradation and deforestation threats, as well as human resource limitations of forestry officers. The Provincial government then initiated stakeholder support, mainly from non-governmental organizations. Social forestry implementation at the site in West Sumatra thus focused on providing development assistance programs after granting management rights to local people, as well as initiating similar schemes in other villages. Our discussions considered challenges that should be addressed, including the approach to granting management rights to secure a management area, the process of developing participatory institutions, synchronizing provincial government policies to overcome forest degradation and deforestation, and initiating activities for strengthening community solidarity and agency.